2006
DOI: 10.1159/000089306
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Fluorescent Polymerase Chain Reaction versus Cytogenetics: Risk-Related Indication and Clinical Implication of Nondetected Chromosomal Disorders

Abstract: Background: The rapid detection of aneuploidies by quantitative fluorescent polymerase chain reaction (QF-PCR) allows reliable prenatal diagnosis of trisomies 21, 18, and 13. Discussion has been raised as to whether single QF-PCR could be an alternative to traditional cytogenetic karyotyping for certain referral categories. Objective: To evaluate an indication-based classification of cases at risk of missing clinically relevant chromosomal disorders by QF-PCR. Methods: From October 1999 to November 2003, 4,682… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Similar to what is observed with NIPS, rapid testing (e.g. QF‐PCR) for the frequent trisomies as a standalone test had been discussed as an alternative to karyotype analysis, but it would miss up to 30% of chromosomal abnormalities depending on the referral indication . When combined screening was introduced, 17% of obstetricians reported that they were offering it as an alternative to amniocentesis (i.e.…”
Section: Discussionmentioning
confidence: 92%
“…Similar to what is observed with NIPS, rapid testing (e.g. QF‐PCR) for the frequent trisomies as a standalone test had been discussed as an alternative to karyotype analysis, but it would miss up to 30% of chromosomal abnormalities depending on the referral indication . When combined screening was introduced, 17% of obstetricians reported that they were offering it as an alternative to amniocentesis (i.e.…”
Section: Discussionmentioning
confidence: 92%
“…Abnormalities such as translocations, deletions, inversions, supernumerary markers, mosaicism, and rare aneuploidies, all of which are detected by G‐banding, are not detectable by QF‐PCR. The detection rate of QF‐PCR versus G‐banded analysis has been studied by numerous groups (Leung et al , 2004; Caine et al , 2005; Ogilvie et al , 2005; Kozlowski et al , 2006; Kagan et al , 2007; Sparkes et al , 2008; Speevak et al , 2008), with results indicating the residual risk of a chromosome abnormality not detected by QF‐PCR in the range of 0.5 to 1.0%.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid prenatal detection of numerical chromosome abnormalities by quantitative fluorescent polymerase chain reaction (QF-PCR) allows for reliable prenatal diagnosis of trisomies 13, 18, and 21 1,2) . QF-PCR is an alternative method for rapid aneuploidy detection (RAD) of common aneuploidies based on the amplification of chromosome-specific DNA short-tandem-repeat (STR) polymorphisms, offering an attractive alternative to fluorescent in situ hybridization (FISH).…”
Section: Introductionmentioning
confidence: 99%